Single-Dose Pharmacokinetics and Safety of Daclatasvir in Subjects with Renal Function Impairment - Garimella, Tushar; Wang, Reena; Luo, Wen-Lin; Hwang, Carey; Sherman, Diane; Kandoussi, Hamza; Marbury, Thomas C; Alcorn, Harry; Bertz, Richard; Bifano, Marc (Antiviral therapy, 2015)
Daclatasvir (DCV) is a pangenotypic inhibitor of the HCV NS5A replication complex approved in Japan and Europe for combination treatment of HCV. AI444-063 was an open-label, two-stage, adaptive study assessing DCV pharmacokinetics and safety in HCV-uninfected subjects with renal impairment. Stage 1 included 12 subjects with end-stage renal disease (ESRD) on dialysis and 12 healthy controls (creatinine clearance [CLcr]≥90 ml/min, Cockcroft-Gault) matched by sex, age and weight. All participants received a single DCV 60-mg dose on day 1. DCV plasma levels were measured through day 4. Prespecified criteria for study expansion (ESRD versus control area under the curve extrapolated to infinite time [AUC∞] geometric mean ratio [GMR] upper 90% CI>1.5) were met; therefore, 12 subjects with moderate or severe renal impairment (estimated glomerular filtration rate, 30-59 and 15-29 ml/min/1.73m(2), respectively) were included in stage 2. All 36 participants (30 male, mean age 54 years) completed the study. DCV AUC∞ was higher in ESRD subjects versus controls (GMR 1.264, 90% CI 0.989, 1.616). Compared with normal CLcr (90 ml/min), GMR and 90% CI for unbound DCV AUC∞ at CLcr 60, 30 and 15 ml/min were 1.18 (1.07, 1.30), 1.39 (1.14, 1.70) and 1.51 (1.18, 1.94), respectively. DCV was generally well tolerated in subjects with normal renal function, ESRD, or moderate or severe renal impairment. Observed DCV exposure increases were within the normal range of variability and were not associated with an elevated risk of adverse events. DCV can be administered in subjects with renal impairment, including ESRD, without dose modification. ClinicalTrials.gov NCT01830205.